Is there any relationship between streptococcal infection and multiple sclerosis? - (:unkn) unknown (INT SCIENTIFIC INFORMATION, INC, 2007)
Background: Multiple sclerosis (MS) is an immune-mediated inflammatory demyelinating disease of uncertain etiology. Although the mechanisms of inducing autoimmunity by some of the infectious agents have been investigated, there is not yet enough research on streptococcal infections. Materials/Methods: To understand the effect of past group A streptococcal infection on MS, antistreptolysin O (ASO) and antideoxyribonuclease B (ADNase B) were measured in 21 patients with relapsing-remitting MS and 21 healthy blood donors by nephelometric assay. Results: ADNase B levels in the patients with MS were found to be significantly higher than in the controls (p<0.001); however, ASO levels were similar in both groups. Conclusions: These findings indicate that a relationship between multiple sclerosis and streptococcal infections may exist, but to acquire a better understanding of the role of group A streptococci in the pathogenesis of multiple sclerosis, more studies with animal models are necessary.
Keywords: multiple sclerosis; etiology; group A streptococci; ASO; ADNase B; ACUTE DISSEMINATED ENCEPHALOMYELITIS